Learning curve for endoscopic submucosal dissection of esophageal neoplasms. Issue 6 (1st September 2016) - Tsou, Y.-K.; Chuang, W.-Y.; Liu, C.-Y.; Ohata, K.; Lin, C.-H.; Lee, M.-S.; Cheng, H.-T.; Chiu, C.-T.
Summary: There is a significant learning curve for endoscopic submucosal dissection of esophageal neoplasms that has not been fully characterized. This retrospective study included 33 consecutive superficial esophageal neoplasms for analysis of the learning curve for esophageal endoscopic submucosal dissection based on a single, novice endoscopist's experience. The study was divided into three periods (T1, T2, and T3) of 10 endoscopic submucosal dissection procedures in chronological order, with 13 procedures in the last period. Patient factors (age, sex, coexistent esophageal varices, or submucosal fibrosis) and tumor factors (location at upper esophagus, involving >3/4 esophageal circumference) for endoscopic submucosal dissection were not statistically different between the periods. The mean procedure time was 74.6 min/cm 2, 23.4 min/cm 2, and 10.5 min/cm 2 for T1, T2, and T3, respectively. The procedure time decreased over time ( P = 0.02) and post hoc test revealed significant difference was only between T3 and T1 ( P = 0.019). The en bloc resection rate was 50%, 100%, and 92.3% for T1, T2, and T3, respectively ( P for trend = 0.015). R0 resection rate was 40%, 100%, and 84.6% for T1, T2, and T3, respectively ( P for trend = 0.023). Two patients had complications: each one patient in T1 and T3 period experienced major bleeding during the procedure ( P for trend = 0.875). None of the patients had esophageal perforation. The results of the study concluded that at least 30 cases of endoscopic submucosal dissection of esophageal neoplasms are needed for a novice endoscopist to gain early proficiency in this technique.